2016
DOI: 10.1515/jpm-2014-0296
|View full text |Cite
|
Sign up to set email alerts
|

Fetal nasal bone length in the second trimester: comparison between population groups from different ethnic origins

Abstract: Normal ranges of fetal nasal bone length in the second trimester vary significantly between different ethnic groups. Hence, distinct ethnic nomograms of fetal nasal bone length in the second trimester should be used in a given population rather than an international model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 3 publications
2
17
0
1
Order By: Relevance
“…Nasal bone absence or hypoplasia in the second trimester can be physiological variations. Studies have also shown that the progress of fetal nasal bone development varies among different ethnic groups . Prefumo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal bone absence or hypoplasia in the second trimester can be physiological variations. Studies have also shown that the progress of fetal nasal bone development varies among different ethnic groups . Prefumo et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of those studies were carried out in high‐risk populations, and only a few in samples representative of the general population. There are variations of fetal nasal bone length among different ethnic groups . So far, there are only a few studies investigating abnormal fetal nasal bone development in the Han Chinese population, with relatively small sample sizes .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the normal ranges of second trimester fetal nasal bone length vary significantly among different ethnic groups [11]. Sonek, et al [12] using the definition of nasal hypoplasia when the nasal bone length is below 3 mm at 16 weeks and 4.5 mm at 20 weeks since the 2.5 th percentiles and 5 th percentiles in the second trimester are quite consistent across studies, reported that the occurrence of absent or hypoplastic fetal nasal bone was 3.66% in their pregnant population at 15-24 weeks of gestation, and the incidence of abnormal nasal bone among Down syndrome cases was 60%.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,19 Similarly, for the 5th percentile of fetal NBL, the present findings differed markedly to data from Southern Asia, but corresponded with the data from Eastern and Southeastern Asia ( Table 3) populations and concluded that fetal NBL varies significantly by race and ethnicity in the second trimester of gestation. 6,7 Normative data for Vietnamese fetal NBL at 19-26 weeks' gestation have been shown to differ from those of other subregions of Asia, including India, China, Japan and Thailand. Maternal ethnicity must therefore be taken into account when using fetal NBL as a marker for aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Based on fetal NBL at the fifth percentile of gestational age in the second trimester, clinicians can predict Down syndrome with a detection rate of 77.7% and a false-positive rate of 0.7%. 4 Racial and ethnic origins have previously been shown to influence fetal NBL: [5][6][7] different normal fetal NBL have been reported for Caucasian, African, Northern Asian and South-Eastern subjects. 5,8,9 In Vietnam, the screening program for Down syndrome based on fetal nuchal translucency and combined test at the first trimester of gestation has been implemented since 2007.…”
Section: Introductionmentioning
confidence: 99%